Time to clinical improvement: an appropriate surrogate endpoint for pulmonary arterial hypertension medication trials - Wang, An; Chen, Mengqi; Zhuang, Qi; Guan, Lihua; Xie, Weiping; Wang, Lan; Huang, Wei; Cheng, Zhaozhong; Yu, Shiyong; Zhou, Hongmei; Shen, Jieyan (Frontiers in Cardiovascular Medicine, 2023)
Background Many retrospective studies suggest that risk improvement may be a suitable efficacy surrogate endpoint for pulmonary arterial hypertension (PAH) medication trials. This prospective multicenter study assessed the efficacy of domestic ambrisentan in Chinese PAH patients and observed risk improvement and time to clinical improvement (TTCI) under ambrisentan treatment. Methods Eligible patients with PAH were enrolled for a 24-week treatment with ambrisentan. The primary efficacy endpoint was 6-min walk distance (Δ6MWD). The exploratory endpoints were risk improvement and TTCI, defined as the time from initiation of treatment to the first occurrence of risk improvement. Results A total of 83 subjects were enrolled. After ambrisentan treatment, Δ6MWD was significantly increased at week 12 (42.2 m, P < 0.0001) and week 24 (53.4 m, P < 0.0001). Within 24 weeks, risk improvement was observed in 53 (64.6%) subjects (P < 0.0001), which is higher than WHO-FC (30.5%) and TAPSE/PASP (32.9%). Kaplan–Meier analysis of TTCI showed a median improvement time of 131 days and a cumulative improvement rate of 75.1%. Also, TTCI is consistent across different baseline risk status populations (log-rank P = 0.51). The naive group had more risk improvement (P = 0.043) and shorter TTCI (log-rank P = 0.008) than the add-on group, while Δ6MWD did not show significant differences between the two groups. Conclusions Domestic ambrisentan significantly improved the exercise capacity and risk status of Chinese PAH patients. TTCI has a relatively high positive event rate within 24-week treatment duration. Compared to Δ6MWD, TTCI is not affected by baseline risk status. Additionally, TTCI could identify better improvements in patients, which Δ6MWD does not detect. TTCI is an appropriate composite surrogate endpoint for PAH medication trials. Clinical Trial Registration NCT No. [ClinicalTrials.gov], identifier [NCT05437224].